2022
DOI: 10.3390/bioengineering9090418
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Soybean Milk Protein by Papain: Antioxidant, Anti-Angiotensin, Antigenic and Digestibility Perspectives

Abstract: The objective of the investigation was to understand the biochemical activities of hydrolysate of soybean milk protein (SMP). Hydrolysis was carried out by different concentrations of papain (0.008 g·L−1, 0.016 g·L−1, 0.032 g·L−1 and 0.064 g·L−1). The antioxidant capacity was measured by the ferric-reducing ability of plasma (FRAP) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assays. The anti-angiotensin activity of hydrolysate was measured by the recombinant angiotensin converting enzyme and substrate Abz-FRK(Dnp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 124 publications
1
2
0
Order By: Relevance
“…Furthermore, as the HHP increased from 200 to 600 MPa, the Mw fractions in the 1-5 kDa range changed slightly. Although the content of the various Mw fractions changed with pressure level, no new Mw fractions were produced, which is consistent with previous work [23]. It has been documented that chickpea hydrolysates by papain under 300 MPa exhibited high antioxidant capacity with peptide fractions of <3 kDa having the highest content, and primarily ranging within 500-1000 Da [40].…”
Section: Peptide Profile Determined By Hpsecsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, as the HHP increased from 200 to 600 MPa, the Mw fractions in the 1-5 kDa range changed slightly. Although the content of the various Mw fractions changed with pressure level, no new Mw fractions were produced, which is consistent with previous work [23]. It has been documented that chickpea hydrolysates by papain under 300 MPa exhibited high antioxidant capacity with peptide fractions of <3 kDa having the highest content, and primarily ranging within 500-1000 Da [40].…”
Section: Peptide Profile Determined By Hpsecsupporting
confidence: 90%
“…Additionally, previous studies reported a higher rising impact of HHP on enzymes under HHP [18]. The peptide profiles in all hydrolysates were expected to be essentially similar to the hydrolysates of native b-LG and b-LG subjected to HHP [23]. In general, HHP treatment of proteins results in high efficiency of proteolysis by various enzymes, which may be attributed to the exposure of cleavage sites of the proteins for the sequential interaction with enzymes [24].…”
Section: Introductionmentioning
confidence: 59%
“…The process of releasing peptides from casein and whey proteins occurs in three ways: through digestive enzymes, through the fermentation process or through the action of proteolytic enzymes, obtained from microorganisms or plants [25][26][27][28]. The plant enzymes are preferred over enzymes of microbial origin mainly due to safety, lack of pathogenicity and other adverse effects [29,30].…”
Section: Bioactive Peptides Have Garnered Huge Scientific Interest Be...mentioning
confidence: 99%